ANALISIS KEPUASAN KERJA KARYAWAN PADA LE MERIDIEN BALI JIMBARAN - ICHA DWI FRICILLIA PALMA; I MADE WIDIANTARA; NI PUTU RITA SINTADEVI (GANEC SWARA, 2023)
The hospitality industry is driven by human resources. Companies must pay attention to employee job satisfaction because it affects employee productivity. The purpose of this study was to determine employee job satisfaction at Le Meridien Bali Jimbaran, to find out what dimensions of employee job satisfaction were not optimal and to find out the efforts to increase employee job satisfaction at Le Meridien Bali Jimbaran. This study collected data using observation, interviews and questionnaires. The analysis technique used are Descriptive Statistics and Importance Performance Analysis. The results of this study show that employee job satisfaction on the expectation indicator is in the very satisfied category, while on the reality indicator it is in the satisfied category, meaning that there is a gap between expectations and actual employee satisfaction. There are six dimensions of job satisfaction that have not been optimal, namely salary, the work itself, co-workers, superiors, promotion and work environment. Efforts to increase employee job satisfaction at Le Meridien Bali Jimbaran by using a work culture, namely clan culture.